Can firms avoid tough patent examiners through examiner‐shopping? Strategic timing of citations in USPTO patent applications. (16th February 2022) - Barber, Benjamin; Diestre, Luis
Abstract: Research summary: We claim that, because patent citations influence examiner selection, firms disclose citations strategically to influence which examiner is assigned to their application ("examiner‐shopping"). Specifically, firms are more likely to cite patents reviewed by "lenient" examiners in their original information disclosure statement (IDS) (sent before the examiner has been selected), and delay citations to patents reviewed by "tough" examiners to subsequent IDS (sent once the examiner has been selected). We propose this strategy will be implemented by those firms who benefit the most (firms that face patent thickets and are developing high strategic‐stakes technologies) but only when the costs are low (when firms face a low probability of patent litigation). We find support to our theory in a sample of 9, 763 United States patent and trademark office (USPTO) patent applications during 2000 to 2006. Managerial summary: We find that firms facing patent thickets and developing high strategic stakes technologies try to get more "lenient" examiners to increase the probability of patent approval. The cost of this strategy is that "lenient" examiners usually grant weaker patents that are more likely to be litigated and invalidated. Firms overcome this by using "examiner‐shopping" mainly in fields where litigation is relatively infrequent. This behavior has relevant implications: fields where property rights are rarely challenged tend to become "denser" and populated by weaker patents. Our study's discussion of the limitations within the United States patent and trademark office (USPTO) that seem to provide the opportunity to implement "examiner‐shopping" strategies provides a path to address this from a policy standpoint.